OPTIMIZATION OF CADETS’ PSYCHOPHYSICAL FITNESS THROUGH INDIVIDUAL TRAINING PROGRAMS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The necessity of individualizing military training for cadets and servicemen is driven by technological advancements and changes in combat tactics. The specialized literature emphasizes the importance and timeliness of an individualized approach; however, the methods of its implementation are not specified. Purpose. The study aims to identify groups of cadets with similar professionally important qualities, develop their characteristics, and justify approaches to individualizing the process of physical training and sports to enhance the effectiveness of military-professional activities. Methodology. A survey was conducted among cadets (n=282) of the Kyiv Institute of the National Guard of Ukraine. The questionnaire included standard methodologies for assessing anxiety levels (STAI), emotional control (Cortlaud Emotional Control Scale), life satisfaction (SWLS, Diener, Emmons, Larsen, and Griffith), and coping strategies (R. Lazarus and S. Folkman). The physical fitness levels of cadets (n=282) were also tested. Descriptive statistics and cluster analysis methods were applied. Results. The cadets were divided into clusters based on their physical fitness and psycho-emotional characteristics. Five groups with relatively homogeneous indicators were identified. We developed "profiles" of psychophysical preparedness. The use of these profiles allowed us to substantiate approaches to individualizing the physical training and sports processes for cadets of five different types to ensure effective military-professional training. During physical training, appropriate physical loads were selected for cadets in each group, considering volume and intensity. Recommendations were provided on suitable physical activities for independent training for cadets of different types. Conclusions. The implementation of an individualized approach to cadets' physical training, particularly through group segmentation, improves their professionally important qualities, enhances physical fitness, and increases competencies in physical education and sports, ultimately contributing to the effectiveness of their military-professional activities.